Nomenclatural notes on Iris songarica (Iridaceae) and two related names - Boltenkov, Eugeny V.; Schröder, Christof N. (Phytotaxa, 2019)
Iris songarica is one of the most widely distributed species of I. ser. Tenuifoliae. Analysis of relevant literature and examination of herbarium material have shown that I. songarica is more variable than reported in the protologue, especially in the number of flowers and the length of the flowering stem, features which are associated with soil and climate of habitat. With up to four branches with 1–3 flowers each, I. songarica differs from all other species of I. ser. Tenuifoliae. For such multi-flowering plants, two names have been proposed: I. songarica var. multiflora and I. multiflora. However, our morphological investigations revealed that these multi-flowering plants fall within the variability of I. songarica. All three names are typified here.